Toxoplasmosis Examination With Anti-Toxo IgM And IgG Results In Petshop Staff - Pratama, Sandi Setya; Kumoro, Adhi (Jurnal Analis Medika Biosains (JAMBS), 2023)
Toxoplasmosis is an infection caused by a single-celled parasite called Toxoplasma gondii.  Infection is most commonly acquired from contact with cats and their feces or raw or undercooked meat. There are several risk factors that favor the occurrence of this infection including the presence of cats in the residence, cleaning of pet litter boxes, hand washing habits and consumption of raw or undercooked food. Petshop is a retail business that sells a variety of pets and also sells pet food, accessories, animal care and maintenance. The purpose of this study was to determine the exposure to toxoplasmosis with the results of Toxoplasma gondii IgG antibody examination and Toxoplasma gondii IgM antibody in petshop staff.This study is a descriptive study using cross sectional method with 25 respondents from petshop staff. The test method for toxoplasmosis detection used was Rapid (Immunochromatography). The data analysis technique used was univariate analysis to determine the percentage of seropositive results of Toxoplasma gondii IgG antibodies and Toxoplasma gondii IgM antibodies. Based on the results of the study obtained data 11 respondents seropositive anti-toxo IgG, 14 respondents did not have anti-toxo IgG and anti-toxo IgM and there were no respondents with positive anti-toxo IgM in Petshop officers. Therefore it can be concluded that 11 out of 25 respondents have been infected with Toxoplasma gondii.